Colon Specific Drug Delivery Systems: A Review on Various Pharmaceutical Approaches - Prasanth V.V, Jayaprakash. R, Sam T. Mathew (Journal of Applied Pharmaceutical Science)
Colon specific drug delivery system has attracted considerable attention for the past few years in order to develop drug delivery systems that are able to release drugs specifically in the colon in a predictable and reproducible manner. The colon is a site where both local and systemic delivery of drugs can take place. To achieve successful colon targeted drug delivery, a drug need to be protected from degradation, release and absorption in the upper portion of the gastric intestinal tract (GIT) and then to be ensured abrupt or controlled release in the proximal colon. This review is aimed at understanding recent approaches for dosage forms which is targeting to colon through pH sensitive system, microbially triggered system i.e., prodrugs and polysaccharide based system, timed release system, osmotically controlled drug system, pressure dependent release system.
Keywords: Colon specific drug delivery, pH sensitive, time controlled dependent, microbially triggered, Pressure controlled and osmotically controlled system.